A study on eye health seeking behaviour among the rural communities in India - Vishwakarma, Pankaj; Mondal, Amit; Ranpise, Dhanaji; Sundararaj, Lijiraj; Shaikh, Shajer; Chavan, Shobhana; Kurian, Elizabeth (International Journal Of Community Medicine And Public Health, 2025)
Background: Eye health is a crucial yet under-prioritized aspect of global public health, with vision impairment affecting 2.2 billion people worldwide, over half of which is preventable or treatable. Despite advancements in eye care, health-seeking behavior remains low in developing regions due to socioeconomic and cultural barriers. Understanding these factors is essential for designing effective interventions. This study examines eye health-seeking behavior across multiple Indian states, identifying key motivators and barriers influencing individuals' decisions to seek eye care. Methods: A cross-sectional study was conducted across eleven Indian states using a multistage random sampling method to ensure diverse representation. A total of 764 participants were surveyed through structured interviews in local languages. The questionnaire covered demographics, barriers, motivators, and eye care behaviours. Data analysis was performed using SPSS and R software. Results: Among 764 participants, 47% were male and 53% female, with 34% aged 50–64 years. While 73% had experienced eye problems, only 14% sought treatment. Financial constraints (36%), lack of awareness (48%), and healthcare accessibility (29%) were major barriers. Cataract (16%), refractive errors (18%), and conjunctivitis (9%) were common diagnoses. Only 6% received free consultations, and 44% lacked health insurance. Cultural beliefs also influenced health-seeking behavior, while community and family support improved engagement. Conclusions: Addressing financial, awareness, and accessibility barriers through targeted campaigns, affordable care, and telemedicine can enhance eye health-seeking behaviour. Community-based interventions and policy support are essential for improving eye care access in underserved regions.